CLOTHING AS THE REFLECTION OF HUMAN RELATION IN THE EPIDEMIC HISTORY - Soonthornpipit , Panchana (Fine Arts Journal: Srinakharinwirot University, 2023)
Humans, as social animals, always rely on their passion and desire to reproduce and live their lives. However, their physical interactions could be the cause of an epidemic, and the rapid spread of such epidemic can prevent us from having physical contact with each other. Under conditions that forced us to be separated from each other, humans have learned to design and produce different types of clothing to help bring them closer together. Surprisingly, when the time passes, certain clothing styles become popular fashion trends. This article investigates the styles and origins of clothing during Epidemic times in the past, such as the Black Death in the Middle Ages, the Spanish flu, the Aids crisis, and the COVID-19 Pandemic, to demonstrate how we, as humans, strive for contact with one another and ultimately achieve it through the use of fashion and clothing.